Improving Knowledge and Changing Health Attitude among Teenagers through Digital Media Flipbook - Erni Gustina; Marsiana Wibowo (Journal of Educational Science and Technology (EST), 2020)
The aims in this study to analyze the effectiveness of digital flipbooks as a medium for health promotion for adolescents. This study is a quasi experimental design with a One Group Pre and Post Test Design. The sample of this study was 100 adolescents.  The average age of adolescents was 16 years and the majority of the female sex. Mean rank for knowledge (Mean rank=2.86; p-value=0.24) and attitude (Mean rank=11.8; p-value = 0.009). Digital media flipbook can influence the attitudes of adolescents but does not affect the change of knowledge. Increase exposure to health promotion programs by expanding access to information about preventing risk behaviors in adolescents to maintain attitudes that avoid adolescents risk behavior.